INTERNALIZATION OF MORAL VALUES IN THE BOOK RASYSY AL-BARAD BY MUḤAMMAD LUQMĀN: A STUDY OF CLASSICAL TEXT-BASED INFORMATION LITERACY - Siagian, Yessy Tesya Ningsih; Arsyad, Junaidi; Sapri, Sapri (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study explores the internalization of moral values contained in Rasysy al-Barad, a classical commentary (syarḥ) on Al-Adab al-Mufrad by Imam al-Bukhārī, through the lens of classical text-based information literacy. The urgency of this research stems from the declining moral behavior among students in Islamic educational institutions, prompting the need to return to foundational ethical texts rooted in prophetic traditions. Using a qualitative descriptive approach with a hermeneutic method, this study analyzes the contents of Rasysy al-Barad and examines the stages of value internalization aligned with the framework of information literacy: accessing, evaluating, and integrating information. The findings reveal that the book emphasizes values such as honesty, trustworthiness, respect, patience, modesty, and compassion. These values are interpreted in relation to contemporary social contexts, reflecting not only textual fidelity but also moral relevance. The study concludes that classical Islamic texts like Rasysy al-Barad function not only as religious knowledge resources but also as character-building tools within Islamic education. It recommends incorporating such texts into values-based curricula to foster moral sensitivity and critical religious thinking (tafaqquh fī ad-dīn), ultimately producing intellectually and ethically grounded individuals.